Electronic waste considerations in the Middle East and North African (MENA) region: A review - Buzaina Moossa (17337883) (2023)
Waste Electrical and Electronic Equipment or e-waste is a waste stream that has multiplied profoundly in recent years. Currently, many researchers focused on the study of e-waste. The Middle East & North Africa (MENA) is a region with similar geographical features, has a high young population, and is economically diverse. The area has seen unprecedented population growth in the last 50 years. This paper presents a review of the reported works in the field of e-waste in the MENA region. It aims to shed light on the various aspects of e-waste in the MENA region. The various methods of estimating the quantities of e-waste, how it is presently managed in the MENA, the impacts of e-waste, and the regulations compliant with MENA are covered in the review. The e-waste stream is beginning to attract attention in certain countries of the MENA in recent years. As a step to this, there are various mathematical models developed to estimate the quantity of e-waste effectively. The prime component of e-waste is mobile phones, which have penetrated very deeply into all regions of the world. The health hazards caused by e-waste stem primarily from heavy metals and halogenated plastics in them. The review found that the health impacts caused by informal e-waste handling in MENA countries are not given due attention and are not covered in the literature. Regarding the regulations on e-waste disposal, countries need to implement these regulations to control e-waste penetration effectively. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eti.2022.102961